2021
DOI: 10.1088/1755-1315/674/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

The digestibility of improved sugar cane bagasse on Barbonymus schwanenfeldii

Abstract: The evaluation of fish capacity to digest an alternative ingredient is a critical aspect. The highly digestible ingredients will improve fish growth performance and reducing the production of wastes. This experiment was conducted to determine the digestibility of improved sugar cane bagasse as an ingredient on Barbonymus schwanenfeldii diet. The nutrient contents of improved sugar cane bagasse were crude protein, lipid, ash, crude fiber, carbohydrates (by difference) of 22.27%, 0.68%, 8.03%, 12.75%, and 55.23%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In a separate study, [27] revealed that hydrolyzed sugarcane bagasse had a digestibility of 66.08% for dry matter, 84.35% for protein, 95.26% for lipid, and 70.49% for energy when fed to Barbonymus schwanenfeldii. These results suggest that hydrolyzed sugarcane bagasse is a reasonably digestible nutritional resource for B. schwanenfeldii and could be incorporated into its diet.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In a separate study, [27] revealed that hydrolyzed sugarcane bagasse had a digestibility of 66.08% for dry matter, 84.35% for protein, 95.26% for lipid, and 70.49% for energy when fed to Barbonymus schwanenfeldii. These results suggest that hydrolyzed sugarcane bagasse is a reasonably digestible nutritional resource for B. schwanenfeldii and could be incorporated into its diet.…”
Section: Resultsmentioning
confidence: 98%
“…Using plant-based protein would increase the reliance on fish meal and fish oil, which is categorized as a non-renewable source [24]. In comparison to locally prevalent plant ingredients typically utilized in feed, such as wheat bran (11.05 %) [25], rice bran (15.23%), and fermented rice bran (17.62%) [26], sugarcane bagasse (1.49%) [27], the protein content (19.28%) in hydrolyzed purslane is relatively higher.…”
Section: Resultsmentioning
confidence: 99%